2018
DOI: 10.1002/ccr3.1708
|View full text |Cite
|
Sign up to set email alerts
|

Management of a failed endodontic treatment for a maxillary second molar with two separate palatal roots

Abstract: Key Clinical MessageComplexity of root canal system and variations in internal anatomy of teeth require careful analysis of preoperative cone beam computed tomography or multiangle radiographs to locate and identify possible extra roots or canals. A fourth canal in upper molars is expected, and much effort should be made when planning the endodontic treatment to avoid missing a canal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(24 reference statements)
0
2
0
1
Order By: Relevance
“…Based on the published findings, the inability to recognize the presence of and to adequately treat all the root canals may lead to high percentages of treatment failure. 1 , 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…Based on the published findings, the inability to recognize the presence of and to adequately treat all the root canals may lead to high percentages of treatment failure. 1 , 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de los estudios están enfocados a la frecuencia de un segundo conducto en la raíz MV (5,6) y solo informes clínicos discuten la presencia de otra raíz palatina (7,8).…”
Section: Discussionunclassified
“…Despite following all procedural protocols, missing a canal or an extra root may lead to treatment failure. [3] Various studies have demonstrated considerable variation in human permanent maxillary molar anatomy. The most common form of the permanent maxillary first molar has three roots and four canals with majority of the mesiobuccal roots having two canals while distobuccal and palatal roots having a single canal.…”
Section: Introductionmentioning
confidence: 99%